Adult brain abscess associated with patent foramen ovale: a case report - Stathopoulos, Georgios T (BioMed Central, 2007)
Brain abscess results from local or metastatic septic spread to the brain. The primary infectious site is often undetected, more commonly so when it is distant. Unlike pediatric congenital heart disease, minor intracardiac right-to-left shunting due to patent foramen ovale has not been appreciated as a cause of brain abscess in adults. Here we present a case of brain abscess associated with a patent foramen ovale in a 53-year old man with dental-gingival sepsis treated in the intensive care unit. Based on this case and the relevant literature we suggest a link between a silent patent foramen ovale, paradoxic pathogen dissemination to the brain, and development of brain abscess.